3 Insitu simulations – fire in a clinical area. (17th November 2016) - Gay, Christopher; Riby, S; Purva, M; Graby, M; Petit, J
Abstract : Background/context: Insitu Simulations offer greatly increased fidelity, but transposing the typical simulation centre video debriefing elements present technical challenges. To date, the majority of HILS's insitu simulations were carried out with clinically led teams and learning objectives. Description of innovation or topic: At HILS we carried out 2 insitu simulations where fire response was the main learning objective. Working with the Trust's Fire Safety Team, real fire alarms were triggered and fake smoke was used, increasing the fidelity greatly. Our technical challenge was to provide a live viewing and video feedback facility for the scenarios. We did this by mixing a range of camera systems -- Mobile SMOTS by Scotia- networked system traditionally used in sim centres GoPro Camera -- Rugged action camera with wide angle lens Google Glass -- head mounted glassed with point of view recording The networked SMOTS camera system used 2 cameras placed in standard scenario locations. The GoPro camera was linked to a HD mobile smots box, which was placed on a corner, utilising its wide angle. These 3 cameras views were all available for live viewing and debriefing. The Google Glass was worn by key actors in the scenario, with footage being made available after debriefing for analysis. Improvements/outcomes (anticipated or recorded) Our improvements were- Introduced additional methods of capturing video into our current insitu simulation routine Bringing a different team into insitu sim, increasing range of subjects covered and fidelity Broadening the learning scope and accuracy of fire procedures Take home messages Mixing technologies can help bridge the difficulties presented by transposing 'normal' simulation methods into the clinical environment. Involving different teams in insitu simulation can focus learning into new areas